PENGGUNAAN MEDIA INTERAKTIF BAAMBOOZLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS DI KELAS VI SDN 1 PAGAR AIR - Fitria Causari; Linda Vitoria; Nurmasyitah Nurmasyitah (STKIP Subang, 2026)
ABSTRACT This research is motivated by the low learning outcomes of students in the Natural and Social Sciences (IPAS) subject of class VI SDN 1 Pagar Air. One effort that can be done to improve student learning outcomes is by using interactive media baamboozle in learning. This study aims (1) to determine teacher activities through the use of interactive media baamboozle (2) to determine student activities through the use of interactive media baamboozle (3) to determine the improvement of student learning outcomes through the use of interactive media baamboozle. This research is a Classroom Action Research (CAR) which was carried out in two cycles. The subjects of the research were all students of class VI B SDN 1 Pagar Air, Aceh Besar Regency, totaling 26 students. Based on the results of the research cycle I and II, the following data were obtained. The percentage of teacher activity in cycle I was 75% with good criteria, increasing in cycle II to 88% with very good criteria. Student activity in cycle I was 61% categorized as sufficient criteria, increasing in cycle II to 83% categorized as very good criteria. The percentage of student learning outcomes before being given the action was 46% categorized as very poor, increased in cycle I to 61% categorized as sufficient, and increased again in cycle II to 88% categorized as very good. Thus, it can be concluded that the use of interactive media baamboozle can improve student learning outcomes in the subject of science.